AB0830 Concordance of the Pase Questionnaire (Psoriatic Arthritis Screening Evaluation) for the Screening and Assessment of Clinical Practice in Psoriatic Arthritis. (9th June 2015) - Torrente-Segarra, V.; Reina, D.; Roig, D.; Cerdà, D.; Estrada, P.V.; Navarro, V.; Peramiquel, L.; García-Díaz, S.; Fíguls, R.; Vidal, D.; Corominas, H.
Abstract : Background: The presence of Psoriasis (PSO) can help you to identify patients with psoriatic arthritis (PsA) at earlier stages of the disease. Early diagnosis in inflammatory arthropathies is crucial to optimize the clinical evolution of our patients. The Psoriatic arthritis screening questionnaire Evaluation (PASE) could help us to accurately identify these patients. Objectives: To assess the concordance of the PASE questionnaire in the screening of PsA in clinical practice and its relationship with the PsA activity measures. Methods: During the 2014 the Dermatology Department has referred all patients with PSO, consecutively, to the Rheumatology Department to evaluate the utility of screening questionnaires PASE for the diagnosis of PsA and to detect articular activity. A score >47 in questionnaire PASE has been shown as a good 'cut-off' score for the suspiction of PsA. Dermatology performed the cutaneous assessment and the PASE. Rheumatology performed the articular assessment, CASPAR criteria completion, PsA diagnosis, DAS28 and BASDAI. We recorded sociodemographics (age, gender) and serological markers (ESR [0-20mmHg], PCR [<3 mg/L]). Results: 75 patients with PSO were referred, 49/45.3% women, mean age 48.9 years. Three patients were diagnosed of PsA (4%), all peripheral disease (2 oligoarticular and 1 monoarticular) and all of them met the CASPAR criteria. Average ESR 9.42 mmHg, average CRP 1.85 mg/L. Seventeen patients (22.6%) had score pass >47, average 55.4 (47-75). A patient (33.3%) with PsA showed PASE<47. Three patients were diagnosed by a rheumatologist of having PsA (sensitivity 17.6%) from those having PASE >47. DAS28 and ANKYLOSING scores: mean DAS28 2.36 (1.6-3.6), mean ANKYLOSING 2.64 (0.08-10). Of these, 7 patients showed DAS28 >2.6, and 7 patients an ANKYLOSING >4 (41.1%). The 3 patients with diagnosis of PsA had BASDAI >4. Conclusions: The PASE questionnaire, pending of expanding the study with a larger number of included patients, did not show as a useful tool particularly in detectin PsA, showing a lower sensitivity than published. The presence of a high PASE, the realization of measures of activity until there be a diagnostic confirmation of APSO by a rheumatologist is not recommended. CASPAR criteria were met in all patients with PsA. As limitation for our findings we might point out: the low prevalence of PsA shown by patients (may be due to the low number of patients included yet) and the clinical practice setting. Disclosure of Interest: None declared